Draft Principles and Guidelines for Integrating Ecosystem-Based Approaches to Adaptation in Project and Policy Design: A Discussion Document. - Andrade Pérez, Angela (2011)
Ecosystem-based approaches to reduce social vulnerability are a promising option for sustainable and efficient adaptation to climate change. Ecosystem based Adaptation (EbA) is part of overall adaptation, and takes into account multiple social, economic and cultural co-benefits for local communities. EbA encompasses adaptation policies and measures that take into account the role of ecosystem services in reducing societal vulnerability, through multi-sectoral and multi-level approaches.